Horror Fiction Dihantui Kendi Maling as an Alternative Discourse to Support the Variety of Literacy Skills of Deaf Students - Yudono, Kristophorus Divinanto Adi; Cahyani, Ayuditya Widya (Unika Santu Paulus Ruteng, 2024)
Horror fiction is still limited to being used as a learning support. Horror fiction works have the opportunity to be alternative learning materials, especially in learning deaf students. In addition to having horror aspects, horror fiction contains a stimulus to strengthen various dimensions of literacy skills. The objectives of this study, among others, (1) Describe the content of literacy dimensions contained in horror stories, (2) Describe the use of horror stories in learning deaf students. The horror story used to support deaf learning is a story entitled Dihantui Kendi Maling by Sylvana Toemon. This research was conducted with a descriptive qualitative approach. The source of research data is horror stories and teaching and learning activities of deaf students. Data was collected by observation techniques, and interviews. Observations are made by participants, or researchers are directly involved in deaf learning. The study participants were deaf teachers and students at SLB B Dena Upakara Wonosobo, Central Java. Interviews are conducted with teachers to clarify or confirm data that does not appear in observations. The results showed that the horror story Haunted by the Maling Jug can be used in learning because it contains a three-dimensional reinforcement stimulus for literacy. The various dimensions of literacy include literacy, financial literacy, and cultural-civic literacy. Literacy is learned through understanding the substance of discourse. Financial literacy is contained in the knowledge of stealing as a form of financial crime. Cultural-civic literacy is found in the attitude of appreciating local knowledge and beliefs in the community. Horror stories and teaching and learning activities are delivered orally as part of the implementation of the Maternal Reflective Method.